AS EFFESIENSI IS INTERVENING? TO FINANCIAL PERFORMANCE IN THE CONSTRUCTION AND SUPPORTERS CORPORATION LISTED ON THE STOCK EXCHANGES OF INDONESIA - Sutriman, Sutriman (JEM17: Jurnal Ekonomi Manajemen, 2019)
This study aims to to analyze the relation of an investment decision, funding decisions and decisions against the efficiency of operational and financial performance. Sampling technique in saturated sampling technique was used in the study, so that it is got 31 service company construction and non-financial supportingya who in pt 2013-2017 the indonesia stock exchange a period of the year. A method of analisi in a pls 2.0 was used in the study. Research results in states that an investment decision, their funding and operational decision decision significant impact on efficiency and financial performance.Keywords : Investment Decision, Financing Decision, Operational Decision, Financial Performance.